Turbomachinery design and theory - Gorla, Rama S.R.; Khan, Aijaz A. (Marcel Dekker New York, 2003)
Presents the theory and design of turbomachines with step-by-step procedures and worked-out examples. This book emphasizes fundamental principles and construction guidelines for enclosed rotators. It evaluates the components of incompressible and compressible fluid flow machines. It analyzes the kinematics and dynamics of turbomachines.
Keywords: Turbomachines